1998
DOI: 10.1540/jsmr.34.13
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Opening and Closure Evaluated by Means of Strain Gauge Force Transducers.

Abstract: Recently, gastrointestinal motility research and various studies to measure motility have been conducted. However , it is not easy to measure the pyloric sphincter motility, especially its open and closed motility . There are few reports on the opening and closed motility of the pyloric ring . In this study, I examined the pyloric motility with strain gauge force transducers (SGTs) . SGTs were implanted onto the antrum , pyloric ring and duode num of a dog. In order to clarify the relationship between the open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…These findings suggest that the indication for PPG in the treatment of early gastric cancer can be extended to radical resection of a group 1 lymph node. It has been reported that pyloric relaxation, recorded under a baseline by the experiment using SG, is observed only in phase III and is synchronized with antral contractions in normal dogs [7]. Our observations in normal dogs are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that the indication for PPG in the treatment of early gastric cancer can be extended to radical resection of a group 1 lymph node. It has been reported that pyloric relaxation, recorded under a baseline by the experiment using SG, is observed only in phase III and is synchronized with antral contractions in normal dogs [7]. Our observations in normal dogs are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the increased frequency of pyloric relaxations during phase II was observed in cholecystectomized dogs. The pyloric ring opens during relaxation of the pyloric sphincter 20 . In humans, the frequency of duodenogastric reflux is negatively correlated with the pyloric pressure 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The highest rate of coordinated contractions occurs in phase III. This is accompanied by reduced resistance in the pylorus due to the action of motilin (22).…”
Section: The Motility Pattern During Fastingmentioning
confidence: 99%